21.9k views
2 votes
How do you prove this trig identity?


\frac{{sec}^(2) \theta - 1}{ {sec}^(2) \theta } = {sin}^(2) \theta

User Jurl
by
5.7k points

1 Answer

1 vote

On the left side, multiply numerator and denominator by
\cos^2\theta:


(\sec^2\theta-1)/(\sec^2\theta)=(\cos^2\theta(\sec^2\theta-1))/(\cos^2\theta\sec^2\theta)=\frac{1-\cos^2\theta}1

which follows from the fact that
\sec\theta=\frac1{\cos\theta}. Then apply the Pythagorean identity,


\sin^2\theta+\cos^2\theta=1\implies(\sec^2\theta-1)/(\sec^2\theta)=\sin^2\theta.

and we're done.

User Mynetx
by
5.4k points